An Electromyographical Approach to Evaluate the Effect of Load on Agricultural Worker during Push–Pull Operation - Kumari, Sweeti; Tewari, V. K.; Kumar, Sanjeev; Sahni, Ramesh K. (Journal of Biosystems Engineering, 48(4), 2023)
Purpose An electromyography (EMG) study was conducted during push and pull operations to evaluate the muscle fatigue of agricultural farm workers. Methods Twelve medically fit agricultural workers were selected for evaluation of muscular activity during push–pull operations, with the help of a laboratory setup, which was developed based on the ergonomic criteria of the uniform force application. The most used muscle during push and pull operation (middle deltoid MD, triceps brachii TR, brachioradialis BR, and biceps brachii BI) was selected for an EMG study. The uniform force or load (50, 100, 150, and 200 N) was applied during the experiment. Results The most activated or used muscles during the pushing and pulling operation were TR and BR, respectively. The activity of the middle deltoid and triceps brachii muscles was more during the pushing than the pulling task. Conclusion Root mean square (RMS) values for EMG activity were found to increase with increasing load in all the selected muscles, indicating that muscular loads were affected by the external load. A load of 200 N was found difficult to operate compared to other selected loads for push–pull operation for all the subjects. The TR muscle gets more fatigued during pushing because it is responsible for elbow extension, which is a primary movement in pushing. The BR muscle gets more fatigued because it is more activated during pull force application.